2016
DOI: 10.21077/ijf.2016.63.2.45664-17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil and source water characteristics of disused shrimp ponds in selected coastal states of India and their suitability for resuming aquaculture

Abstract: The key objective of this study was to assess the suitability of soil and source water quality of abandoned shrimp farms in selected coastal states of India, for resuming aquaculture activities. Soil samples along with associated source water were collected from 60 disused shrimp ponds in different districts of Andhra Pradesh, Tamil Nadu, Odisha and Kerala and analysed for basic physico-chemical parameters. Results of the analysis indicated that the reason for disuse might be reduction in price/repeated occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…S1b). The organic carbon levels in eight APS were similar to the findings of Saraswathy et al (2016) who reported organic carbon levels in sediment between 0Á81 and 1Á02% in traditional shrimp ponds of Kerala and Sahu et al (2007) showed sediment organic carbon levels of 1-1Á5% in polyculture farms with a combination of inputs including fertilizers, supplementary feed, periphytic substrate etc. In the present study, concentration of organic carbon in R-ponds was relatively higher (1Á4-2Á3%) than C-ponds, which might be due to the inappropriate supplementation of chicken slaughter waste as a feed to the cultured fishes.…”
Section: Environmental Factors In the Apssupporting
confidence: 84%
See 2 more Smart Citations
“…S1b). The organic carbon levels in eight APS were similar to the findings of Saraswathy et al (2016) who reported organic carbon levels in sediment between 0Á81 and 1Á02% in traditional shrimp ponds of Kerala and Sahu et al (2007) showed sediment organic carbon levels of 1-1Á5% in polyculture farms with a combination of inputs including fertilizers, supplementary feed, periphytic substrate etc. In the present study, concentration of organic carbon in R-ponds was relatively higher (1Á4-2Á3%) than C-ponds, which might be due to the inappropriate supplementation of chicken slaughter waste as a feed to the cultured fishes.…”
Section: Environmental Factors In the Apssupporting
confidence: 84%
“…Lowest pH was recorded in R9 (pH-3Á0) followed by R3 (pH-3Á1) and R7 (pH-3Á3). The acidic nature of shrimp culture ponds of Kerala, India was reported earlier by several authors (Krishnani et al 2011;Saraswathy et al 2016;Sahadevan and Sureshkumar 2020). Microbial activity is higher in aquaculture pond sediments with a pH range of 7Á5-8Á0 which favours the decomposition of organic matter and also hastens the nutrient recycling process (Boyd and Pippopinyo 1994).…”
Section: Environmental Factors In the Apssupporting
confidence: 57%
See 1 more Smart Citation
“…Countries like China, Egypt and Israel, are known to efficiently utilize this resource for increasing aquaculture productivity (FAO, 2018). Besides these resources, India holds about 40,000 hectares of abandoned shrimp ponds which can be used for culture of E. suratensis, seabass and mullet with the minor technological intervention (Ravisankar et al, 2014 andSaraswathy et al, 2016).…”
Section: Land and Water Availabilitymentioning
confidence: 99%
“…In the shrimp hatchery, unpolluted seawater is required for brood stock maintenance, spawning, larval rearing and culture of food organism. The grow-out farm ponds need sea/brackish water, free from agriculture, domestic and industrial pollution and also within the required salinities, pH and temperature ranges (Saraswathy et al 2016). The fact understood is that the effect of pollution from shrimp farm effluent is considerably less than that of domestic or industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%